Genetic diversity and mating system analysis of Cedrela odorata L. (Meliaceae) populations under different human dominated landscapes and primary forests - Hernández Sánchez, Luis G. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (Mag. Sc.) -- CATIE, Turrialba (Costa Rica), 2008